Live Donor Renal Anatomic Asymmetry and Posttransplant Renal Function. Issue 8 (August 2015) - Tanriover, Bekir; Fernandez, Sonalis; Campenot, Eric S.; Newhouse, Jeffrey H.; Oyfe, Irina; Mohan, Prince; Sandikci, Burhaneddin; Radhakrishnan, Jai; Wexler, Jennifer J.; Carroll, Maureen A.; Sharif, Sairah; Cohen, David J.; et al.
Abstract : Background: Relationship between live donor renal anatomic asymmetry and posttransplant recipient function has not been studied extensively. Methods: We analyzed 96 live kidney donors, who had anatomical asymmetry (>10% renal length and/or volume difference calculated from computerized tomography angiograms) and their matching recipients. Split function differences (SFD) were quantified with technetium-dimercaptosuccinic acid renography. Implantation biopsies at time 0 were semiquantitatively scored. A comprehensive model using donor renal volume adjusted to recipient weight (Vol/Wgt), SFD, and biopsy score was used to predict recipient estimated glomerular filtration rate (eGFR) at 1 year. Primary analysis consisted of a logistic regression model of outcome (odds of developing eGFR>60 mL/min/1.73 m 2 at 1 year), a linear regression model of outcome (predicting recipient eGFR at one-year, using the chronic kidney disease-epidemiology collaboration formula), and a Monte Carlo simulation based on the linear regression model (N=10, 000 iterations). Results: In the study cohort, the mean Vol/Wgt and eGFR at 1 year were 2.04 mL/kg and 60.4 mL/min/1.73 m 2, respectively. Volume and split ratios between 2 donor kidneys were strongly correlated (r = 0.79, P < 0.001). The biopsy scores among SFD categories (<5%, 5%–10%, >10%) were not different ( P = 0.190). On multivariate models, only Vol/Wgt was significantly associated with higher odds of having eGFR > 60 mL/min/1.73 m 2 (odds ratio, 8.94, 95% CI 2.47–32.25, P = 0.001) and had a strong discriminatory power in predicting the risk of eGFR less than 60 mL/min/1.73 m 2 at 1 year [receiver operating curve (ROC curve), 0.78, 95% CI, 0.68–0.89]. Conclusions: In the presence of donor renal anatomic asymmetry, Vol/Wgt appears to be a major determinant of recipient renal function at 1 year after transplantation. Renography can be replaced with CT volume calculation in estimating split renal function. Abstract : Live donor renal anatomic asymmetric correlates with recipient renal function, and CT volume calculation is as accurate as split function testing to quantify differences. Supplemental digital content is available in the text.